1998
DOI: 10.1021/bi972530m
|View full text |Cite
|
Sign up to set email alerts
|

Protein Component of Bacillus subtilis RNase P Specifically Enhances the Affinity for Precursor-tRNAAsp

Abstract: Ribonuclease P (RNase P) is an endonuclease that cleaves precursor tRNA to form the 5'-end of mature tRNA and is composed of a catalytic RNA subunit and a small protein subunit. The function of the protein component of Bacillus subtilis RNase P in catalysis of B. subtilis precursor tRNAAsp cleavage has been elucidated using steady-state kinetics, transient kinetics, and ligand affinity measurements to compare the functional properties of RNase P holoenzyme to RNase P RNA in 10 mM MgCl2, 100 mM NH4Cl. The prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

17
211
1
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 160 publications
(230 citation statements)
references
References 43 publications
17
211
1
1
Order By: Relevance
“…Although the RNA component alone is capable of catalyzing pre-tRNA cleavage in high salt in vitro, the protein is essential for catalytic activity in vivo (Hsieh et al 2004;Evans et al 2006;Gossringer et al 2006;Smith et al 2007). In vitro studies indicate that the P protein subunit contributes to numerous facets of RNase P catalysis including substrate and metal affinity and cleavage efficiency (Reich et al 1988;Crary et al 1998;Kurz et al 1998;Sun et al 2006). For example, P protein enhances k cat /K m for Bacillus subtilis RNase P-catalyzed cleavage by 2000-fold and substrate affinity by 10 4 -fold (Kurz et al 1998), while the homologous protein subunit of Escherichia coli RNase P increases the cleavage rate constants for some noncanonical pre-tRNA substrates by >900-fold (Sun et al 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the RNA component alone is capable of catalyzing pre-tRNA cleavage in high salt in vitro, the protein is essential for catalytic activity in vivo (Hsieh et al 2004;Evans et al 2006;Gossringer et al 2006;Smith et al 2007). In vitro studies indicate that the P protein subunit contributes to numerous facets of RNase P catalysis including substrate and metal affinity and cleavage efficiency (Reich et al 1988;Crary et al 1998;Kurz et al 1998;Sun et al 2006). For example, P protein enhances k cat /K m for Bacillus subtilis RNase P-catalyzed cleavage by 2000-fold and substrate affinity by 10 4 -fold (Kurz et al 1998), while the homologous protein subunit of Escherichia coli RNase P increases the cleavage rate constants for some noncanonical pre-tRNA substrates by >900-fold (Sun et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…In vitro studies indicate that the P protein subunit contributes to numerous facets of RNase P catalysis including substrate and metal affinity and cleavage efficiency (Reich et al 1988;Crary et al 1998;Kurz et al 1998;Sun et al 2006). For example, P protein enhances k cat /K m for Bacillus subtilis RNase P-catalyzed cleavage by 2000-fold and substrate affinity by 10 4 -fold (Kurz et al 1998), while the homologous protein subunit of Escherichia coli RNase P increases the cleavage rate constants for some noncanonical pre-tRNA substrates by >900-fold (Sun et al 2006). Both E. coli and B. subtilis proteins also decrease the concentration of divalent metal ions required for catalysis by RNase P (Gardiner et al 1985;Kurz et al 1998;Sun and Harris 2007), perhaps by stabilizing an essential metaldependent conformational change (Hsieh et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The holoenzyme of a bacterial RNase P is a ribonucleoprotein complex containing an RNA component (P RNA) of ;330-420 nt and a protein component (P protein) of ;120 amino acids (Frank & Pace, 1998;Altman & Kirsebom, 1999)+ The functional role of the protein component in the RNase P holoenzyme has been investigated extensively (Guerrier-Takada et al+, 1983, 1984Gardiner et al+, 1985;McClain et al+, 1987;Reich et al+, 1988;Peck-Miller & Altman, 1991;Svard & Kirsebom, 1992;Tallsjo & Kirsebom, 1993;Liu & Altman, 1994;Crary et al+, 1998;Kurz et al+, 1998;Loria et al+, 1998;Niranjanakumari et al+, 1998aNiranjanakumari et al+, , 1998bLoria & Pan, 1999)+ The Bacillus subtilis RNase P holoenzyme is remarkably efficient in the catalysis of precursor tRNA substrates with a k cat /K m near the diffusion limit (Kurz et al+, 1998;Reich et al+, 1988)+ In the absence of the protein component, k cat /K m decreases by 10 4 -fold under physiological conditions (Kurz et al+, 1998)+ A principal effect of the P protein function has been postulated to be the enhancement of substrate binding under physiological conditions (Crary et al+, 1998;Kurz et al+, 1998;Niranjanakumari et al+, 1998b)+ The physical state of the RNase P holoenzyme has received less attention+ Previous work by the Altman group conclusively showed that the Escherichia coli holoenzyme has an equal molar amount of RNA and protein (Talbot & Altman, 1994a)+ The affinity of the P protein binding to P RNA has been estimated to be ;0+5 nM, assuming a simple two-component binding isotherm (Talbot & Altman, 1994b)+ Functional studies by the Fierke group showed that the RNA-protein stoichiometry of the B. subtilis holoenzyme is also 1:1 (Niranjanakumari et al+, 1998a)+ Most studies in this area have focused on the details of P RNA-P protein interactions using chemical modification (Vioque et al+, 1988;Talbot & Altman, 1994b;Loria et al+, 1998;Biswas et al+, 20...…”
Section: Introductionmentioning
confidence: 99%
“…Transfer RNA (tRNA) molecules are synthesized as precursors possessing both 59-leader and 39-trailer extensions+ Ribonuclease P (RNase P) is a ubiquitous enzyme required for maturation of precursor tRNA (pre-tRNA) by endonucleolytic cleavage between the 59-leader and the mature tRNA domain+ In all varieties of RNase P studied previously, the enzyme is composed of an RNA subunit and a protein subunit+ In bacteria, it is the RNA component alone that is responsible for catalysis (Guerrier-Takada et al+, 1983), whereas in eukaryal and archaeal varieties of RNase P, both subunits are required for activity (for review, see Pace & Brown, 1995)+ The bacterial RNase P protein subunit contains an average of 120 amino acids and the RNA subunit is 350-400 nt long (Brown & Pace, 1992)+ For example, the Escherichia coli RNase P protein has a chain length of 119 nt (13+8 kDa) whereas the RNA subunit is 377 nt (146 kDa)+ The role of the protein subunit is to facilitate binding of the anionic substrate and enzyme in vivo; and to alter substrate versus product-binding kinetics to permit enzyme discrimination between substrate and product (Reich et al+, 1988;Tallsjö & Kirsebom, 1993;Kurz et al+, 1998)+ Bacterial RNase P is a metalloenzyme, requiring divalent metal cations for activity+ The divalent ion functions directly in catalysis, as the RNA subunit can bind substrate in the presence of monovalent ions alone, and displays a burst of activity once a divalent species is added (Smith et al+, 1992)+ Three Mg 2ϩ ions participate in catalysis (Hardt et al+, 1993;Smith & Pace, 1993;Beebe et al+, 1996;Chen et al+, 1997)+ Magnesium(II) is thought to promote catalysis in two ways; by coordinating phosphate oxygen molecules and polarizing the phosphorus center, and by activating the nucleophilic water molecule that attacks the scissile bond (Smith & Pace, 1993;Fersht, 1985)+…”
Section: Introductionmentioning
confidence: 99%